Enhancing Occupational Safety in AI-Driven Supply Chains: Challenges and Solutions - Raman, Rohit; Shrivastava, Rashmi (International Journal of Supply Chain and Logistics, 2025)
Purpose: This paper explores the transformative impact of Artificial Intelligence (AI) and robotics in the fifth industrial revolution, particularly post-pandemic, where their adoption has significantly streamlined operations, reduced costs, and enhanced product development and distribution. Despite these advantages, their widespread use raises concern about occupational safety, including worker injuries and psychological harm. Methodology: A systematic literature review was conducted to trace the evolution of workplace hazards and identify emerging risks associated with AI and robotics. The study also assessed strategies for mitigating these risks and evaluated the effectiveness of current regulatory frameworks in promoting occupational safety. Findings: The research highlights that while AI and robotics reduce certain traditional workplace hazards, they introduce new risks such as human-robot collisions, algorithmic bias, and unintended consequences. Regulatory bodies are pivotal in developing and enforcing policies to safeguard workers. Additionally, organizations, AI developers, and individuals must collaborate to create safer workplaces. Unique Contribution to Theory, Policy and Practice: This study contributes to the understanding of occupational safety in AI and robotics by identifying emerging risks, suggesting strategies for human-robot collaboration, and offering regulatory recommendations. It emphasizes a multi-stakeholder approach to ensure safe and effective integration of these technologies in the workplace.